The effect of perceived teachers’ interpersonal behavior on students’ learning in physical education: a systematic review - Tian, Lijun; Shen, Jun (Frontiers in Psychology, 2023)
The primary purpose of this study was to conduct the first systematic review on teachers' interpersonal behaviors and students' learning within the physical education context. We searched the English literature in the EBSCOhost, Web of Science, SCOPUS and PubMed electronic databases and following screening, data extraction, quality assessment, 35 published articles were included in this review. The results showed that: perceived teachers' supportive behaviors have effect on autonomous motivation of students, and perceived teachers' controlling behaviors have effect on students' controlling motivation and amotivation, the influencing mechanism may be that teachers' interpersonal teaching behaviors make students' basic psychological needs satisfaction or frustration; perceived teachers' international behaviors have effect on PE learning emotion of students, and perceiving teachers' supportive behaviors can trigger students' positive learning emotion, on the contrary, perceiving teachers' controlling behaviors can stimulate students' negative learning emotion; teachers' interpersonal behaviors have effect on students' psychological well-being and physical activity levels in class with the evidence insufficient, and more evidence are needed. It is extremely necessary to expand such study direction and strengthen better quality study to explore the effect of teachers' interpersonal behaviors on learning process and learning outcome in physical education class, and examine the indirect influence mechanism through that the relationship is connected. The present review provides preliminary evidence to enhance the quality of physical education teaching in class, promote students' academic performance by intervening teachers' interpersonal behaviors.